Exploring the impact of age, sex and life experiences on plasma inflammatory profiles through comparative proteomics - Bartolucci, Martina; Utyro, Olga; Muraglia, Anita; Repetto, Alessia; Agostini, Vanessa; Pizzonia, Monica; Ottaviani, Silvia; Tripodi, Gino; Filaci, Gilberto; Cancedda, Ranieri; Petretto, Andrea; Mastrogiacomo, Maddalena (Frontiers in Immunology, 2026)
BackgroundIn the heterochronic parabiosis model it has been shown that blood from elderly animals exhibits markedly reduced rejuvenating effects compared to that of young organisms. Furthermore, human plasma from older subjects, when used as a supplement in cell culture media, is significantly less effective than plasma derived from younger individuals. This study analyzed plasma from a cohort of 229 subjects by a proteomic approach to reveal age-related changes.MethodsA mass spectrometry-based proteomic analysis was performed on plasma samples from 3 age-groups: a prepubertal, a healthy young adult group and a cohort of individuals over 75 years old with three different life-experiences. An additional parallel study was conducted by a Milliplex Luminex assay.ResultsThe proteomic analysis revealed a chronic inflammatory state in the elderly population, along with complement activation and impaired regulation of blood coagulation. This inflammatory condition was confirmed by Luminex assay, showing elevated levels of classical pro-inflammatory cytokines in the plasma of elderly individuals. Moreover, the elderly group showed a reduced production of antibody light chains, suggesting concurrent immunosenescence. In the older group we identified 25 upregulated proteins whose elevated abundance, combined with acquired immune aging may constitute a plasma proteomic signature of aging. The degree of upregulation of these signature proteins varied among elderly subgroups with different life-experience. A good physical condition and/or cognitive function correlated with a lower expression of the aging-related proteomic profile. Furthermore, several sex-specific differences were identified in the plasma profiles of young donors. Reversely, among elderly individuals, no major differences were observed, except for an increased level of Pregnancy Zone Protein (PZP) in females.ConclusionsProteomic analysis of plasma revealed protein variations associated with aging, primarily involving inflammation-related pathways, immunosenescence features, and sex-linked differences. This study highlights the pathological characteristics underlying the aging process.